Artificial nutrition in patients with cancer has no impact on tumour glucose metabolism: Results of the PETANC Study. Issue 5 (October 2019) - Deshayes, Emmanuel; de Forges, Hélène; Fraisse, Julien; Eberlé, Marie-Claude; Guillemard, Sophie; Fallières, Anne; Pouget, Jean-Pierre; Tétreau, Raphaël; Kotzki, Pierre-Olivier; Santoro, Lore; Senesse, Pierre; Flori, Nicolas
Summary: Background & aims: Nutrition support is recommended in cachexic patients with cancer. However, there is no clear evidence about its impact on tumour growth. Glycolysis, which is usually higher in cancer than normal cells, can be monitored by 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) imaging that is widely used for cancer staging and therapy efficacy assessment. Here, we used 18 F-FDG PET/CT imaging to investigate whether artificial nutrition has an impact on tumour glucose metabolism in patients with cancer and cachexia. Methods: This prospective study included ten patients with histologically proven head and neck or oesophageal cancer. All patients underwent 18 F-FDG PET/CT imaging at baseline and after (parenteral and/or enteral) nutrition support on average for 7 days. Tumour glucose metabolism changes were evaluated using static (SUVmax, SUVmean and SULpeak ) and dynamic (glucose metabolic rate and transport constant rates, k) parameters computed from the 18 F-FDG PET/CT data. Results: Artificial nutrition (median energy intake of 21.83 kcal/kg/day [13.16–45.90], protein intake of 0.84 g/kg/day [0.56–1.64]) was administered. Eight patients (80%) received enteral nutrition and two patients (20%) parenteral support. Comparison of 18 F-FDG PET/CT parameters did not highlight any significant difference in tumour glucose metabolism before and after the period of nutrition support. Conclusions: In cachexic patients with head and neck or oesophageal cancer, nutrition support administered according to the current guidelines shows no impact on tumour glucose metabolism, assessed by 18 F-FDG PET/CT.